2022
DOI: 10.1507/endocrj.ej21-0573
|View full text |Cite
|
Sign up to set email alerts
|

Do the benefits of sodium-glucose cotransporter 2 inhibitors exceed the risks in patients with type 1 diabetes?

Abstract: Sodium-glucose cotransporter 2 inhibitors (SGLT2is) are well-established means of improving glycemia and preventing cardio-renal events in patients with type 2 diabetes. However, their efficacy and safety have yet to be fully characterized in patients with type 1 diabetes (T1D). We studied patients with T1D who regularly attended one of five diabetes centers and treated with an SGLT2i (ipragliflozin or dapagliflozin) for >52 weeks, and the changes in HbA1c, body mass, insulin dose, and laboratory data were ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Secondary analyses of mentioned trials have also revealed potential nephroprotective effects of flozins that are independent of improved glycaemic control [ 64 ]. However, the study conducted by Komoshima et al revealed that adding SGLT2is to intensive insulin treatment in patients with T1DM improves glycaemic control and body mass without increasing the incidence of DKA and hypoglycaemic events [ 65 ]. Additional research is required to determine nephro- and cardioprotective effects of SGLT-2is added to insulin treatment and whether these beneficial effects exceed the risk of DKA.…”
Section: Sglt-2is As a Drug Classmentioning
confidence: 99%
“…Secondary analyses of mentioned trials have also revealed potential nephroprotective effects of flozins that are independent of improved glycaemic control [ 64 ]. However, the study conducted by Komoshima et al revealed that adding SGLT2is to intensive insulin treatment in patients with T1DM improves glycaemic control and body mass without increasing the incidence of DKA and hypoglycaemic events [ 65 ]. Additional research is required to determine nephro- and cardioprotective effects of SGLT-2is added to insulin treatment and whether these beneficial effects exceed the risk of DKA.…”
Section: Sglt-2is As a Drug Classmentioning
confidence: 99%